A multiple reaction monitoring (MRM) method to detect Bcr-Abl kinase activity in CML using a peptide biosensor. - Tzu-Yi Yang; Christie L Eissler; Mark C Hall; Laurie L Parker (PLoS ONE, 2013)
The protein kinase Bcr-Abl plays a major role in the pathogenesis of chronic myelogenous leukemia (CML), and is the target of the breakthrough drug imatinib (Gleevec™). While most patients respond well to imatinib, approximately 30% never achieve remission or develop resistance within 1-5 years of starting imatinib treatment. Evidence from clinical studies suggests that achieving at least 50% inhibition of a patient's Bcr-Abl kinase activity (relative to their level at diagnosis) is associated with improved patient outcomes, including reduced occurrence of resistance and longer maintenance of remission. Accordingly, sensitive assays for detecting Bcr-Abl kinase activity compatible with small amounts of patient material are desirable as potential companion diagnostics for imatinib. Here we report the detection of Bcr-Abl activity and inhibition by imatinib in the human CML cell line K562 using a cell-penetrating peptide biosensor and multiple reaction monitoring (MRM) on a triple quadrupole mass spectrometer. MRM enabled reproducible, selective detection of the peptide biosensor at fmol levels from aliquots of cell lysate equivalent to ~15,000 cells. This degree of sensitivity will facilitate the miniaturization of the entire assay procedure down to cell numbers approaching 15,000, making it practical for translational applications in patient cells in which the limited amount of available patient material often presents a major challenge.